Difficulty in Distance Learning at the High Basic Level in Light of the Corona Pandemic in Directorate of Education/ Bani Kenana Metropolitan as perceived by students - Kanaan, Mustafa Muhamed Hadi (Journal of Educational and Psychological Sciences, 2021)
The purpose of this study was to identify the difficulty of distance learning at the High Basic Level According to the Gender and Class Variables in Light of the Corona Pandemic in Directorate of Education/ Bani Kenana Metropolitan as perceived by students. To achieve this, the researcher used the descriptive analytical approach by constructing a questionnaire which consists of (37) items, that consisted of two main areas, which are difficulty to technical technologies and infrastructure for remote e-learning, and between the level of student interaction for e-learning via the google docs, due to the difficulty of reaching school students due to the Corona pandemic. The results revealed that there were no statistically significant differences at the level of significance (α≤0.05) between the estimates of the study sample individuals. There were no statistically significant differences at the level of significance (α≤0.05) between the estimates of the study sample individuals for the difficulty of technical technologies and the e-learning infrastructure distance, and the level of student interaction for e-learning via distance. In addition to the absence of statistically significant differences at the level of significance (α≤0.05) between the study sample’s estimates of the difficulty to distance learning at the high basic level according to the gender and class variables in Light of the Corona Pandemic in Directorate of Education/ Bani Kenana Metropolitan as perceived by students, the study recommended improving the work of the Darsak platform in cooperation with teachers from within the field, and conducting studies on continuity of work through learning and e-learning from a distance and that each school has its own platform.